Autologous Fat Grafting Combined with Facelifting - Tzikas, Thomas (Facial Plastic Surgery, 2017)
There are multiple factors contributing to facial aging. Rejuvenation of the aging face, therefore, requires a multimodal approach to attain an overall natural and uniform result that is long lasting. Fat grafting has become a very important method for restoring facial soft-tissue atrophy, while facelifting procedures address the ptosis and descent of facial and neck tissue. These modalities performed together offer the patient a comprehensive approach to attain a more attractive and youthful facial appearance.
Keywords: fat grafting; fat transfer; autologous fat grafting; facelift; volume enhancement; fat augmentation; facial rejuvenation